Potrait Legal Protection Women’s Human Rights Through the Establishment of Gender Mainstreaming Local Regulations - Evendia, Malicia; Arif Firmansyah, Ade; Saifullah, Ulinnuha (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
Human rights are basic rights inherent in every human being, including women. However, the stigmatization of women, which often makes the appearance of women's human rights limited, makes it difficult for them to develop themselves. Based on data from the UNDP Gender Inequality Index, Indonesia occupies the highest score in ASEAN with a gender inequality percentage of 48%. The participation of women in development is one of the reasons for the high preference for gender. The government has made various efforts to improve the dignity of women, one of which is through gender mainstreaming. In the context of decentralization, local governments need to elaborate on gender mainstreaming policies in local regulations as an effort to protect women's human rights laws in the regions. This paper aims to portray legal protection through gender mainstreaming within the framework of regional autonomy. The results of the study show that: first, local governments have the authority and responsibility in realizing gender-responsive regional development, both based on local government legal regimes and sectoral legal regimes. Regional autonomy should be able to address gender in accordance with the locality of the region. Second, gender mainstreaming is a necessity as well as a challenge for local governments, in the optics of law as a means of development, regional regulations regarding gender mainstreaming become the juridical basis for regions to ensure and realize conditions of gender equality at the regional level; increasing the contribution and role of women in the regions; and encourage gender-responsive regional development as a form of efforts to protect and fulfill women's rights.